Chitosan-driven biocompatible hydrogel based on water-soluble polypyrrole for stable human-machine interfaces. (1st November 2022) - Wang, Chengyu; Zhang, Jin; Xu, Hao; Huang, Caihua; Lu, You; Cui, Hongyue; Tan, Yebang
Abstract: Recently, wearable hydrogel sensors based on polypyrrole have shown considerable promise in the realms of human-machine interfaces. However, because of the water insolubility of pyrrole and polypyrrole, the preparation of polypyrrole conductive hydrogels with comprehensive properties by a simplified method remains a great challenge. Herein, the water-soluble polypyrrole was synthesized and the conformal C x P y conductive hydrogels were fabricated by the strategy of one-pot method of introducing chitosan and water-soluble polypyrrole into acrylamide matrix containing cucurbit[7]uril. The hydrogel exhibited good mechanical strength (215.48 kPa at the fracture strain of 2149.17 %), superior adhesion strength (~51.54 kPa), excellent conductivity (0.534 S m −1 ) and biocompatibility (The cell viability of NIH3T3 is 98.25 %). As a strain sensor, C10 P5 hydrogel exhibited excellent stability during 1000 times cycles, which is suitable for epidermal sensors to monitor body motions and physiological signals. Therefore, the chitosan-driven conductive hydrogel would present prosperous prospects in the fields of human-machine interfaces. Graphical abstract: Chitosan-driven biocompatible hydrogels based on water-soluble polypyrrole and cucurbit[7]uril were prepared by the one-pot method. They present prosperous prospects in the fields of human-machine interfaces. Unlabelled Image